Academic production patterns in public administration: An analysis based on scopus (2017)
This study analyzes the academic production on public administration for the period between January, 1930 and June, 2016 with emphasis on production from 2010 to June 2016. For this purpose descriptive bibliometric indicators will be used: volume of production, typology of documents, number of citations, institutional affiliation of the researchers, sources, main journals, countries of origin of the researchers and the H, G, R, i10 and A indices from the records of the Scopus bibliographic index.